(untitled) (Research, Society and Development, 2021)
SARS-CoV-2 is part of the betacoronavirus family group, responsible for the highest morbidity and mortality rates in the population. In March 2020 the world entered a state of emergency due to a pandemic by betacoronavirus that causes Covid-19 disease, so there is a search for effective therapies for pandemic control. Apitoxin has aroused interest in the possibility of its use in the modulation of the immune system in the inactivation of viruses. In this sense, the main objective of the research project was to analyze the use of apitoxin as an auxiliary tool in the prophylaxis of infection caused by SARS-CoV-2. The apitoxin was obtained from bees belonging to the species Apis Mellifera, by means of electric shock. In the execution of the assays, rats belonging to the Wistar species were used, with approximately 350g of weight and all of the same lineage. 15 animals were used in the experiments. The dose of apitoxin inoculated in the animals was 30 μg/mL Blood collection in the animals was performed in triplicate randomly, in the time intervals of 7, 14, 21 and 28 days. Serological tests were performed by immunochromatographic method for SARS-CoV-2. The results demonstrated the production of IgM anti- SARS-CoV-2, in the time intervals in which the blood collections of the animals were made. Therefore, the apitoxin in the concentration used, in fact induced the production of antibodies belonging to the IgM class against SARS-CoV-2 in animal models and can be used as an auxiliary tool in the modulation of the immune system against the virus that causes Covid-19.